Spin 3-Body Problem Of Classical Electrodynamics In The 3D-Kepler Form (Letters in Nonlinear Analysis and its Applications, 2024)
In the present paper we prove the existence of spin functions for 3-body problem of classical electrodynamics. It is a direct continuation of a previous paper in which we proved the existence and uniqueness of a periodic solution to the same problem in 3D Kepler form. To prove the existence of periodic spin functions we use fixed point method for operator equations.
Keywords: spin functions; classical electrodynamics; three-body problem; periodic solutions; fixed point method